Convergence of Daily GRACE Solutions and Models of Submonthly Ocean Bottom Pressure Variability - Schindelegger, Michael; Harker, Alexander A.; Ponte, Rui M.; Dobslaw, Henryk; Salstein, David A. (FID GEO, 2021)
Knowledge of submonthly variability in ocean bottom pressure (pb) is an essential element in space‐geodetic analyses and global gravity field research. Estimates of these mass changes are typically drawn from numerical ocean models and, more recently, GRACE (Gravity Recovery and Climate Experiment) series at daily sampling. However, the quality of pb fields from either source has been difficult to assess and reservations persist as to the dependence of regularized GRACE solutions on their oceanographic priors. Here, we make headway on the subject by comparing two daily satellite gravimetry products (years 2007–2009) both with each other and with pb output from a diverse mix of ocean models, complemented by insights from bottom pressure gauges. Emphasis is given to large spatial scales and periods <60 days. Satellite‐based mass changes are in good agreement over basin interiors and point to excess pb signals (∼2 cm root‐mean‐square error) over Southern Ocean abyssal plains in the present GRACE de‐aliasing model. These and other imperfections in baroclinic models are especially apparent at periods <10 days, although none of the GRACE series presents a realistic ground truth on time scales of a few days. A barotropic model simulation with parameterized topographic wave drag is most commensurate with the GRACE fields over the entire submonthly band, allowing for first‐order inferences about error and noise in the gravimetric mass changes. Estimated pb errors vary with signal magnitude and location but are generally low enough (0.5–1.5 cm) to judge model skill in dynamically active regions. : Plain Language Summary: Changes in the pressure at the seafloor tell us how ocean masses move in time and space. These environmental signals are important for understanding variations in Earth's shape, rotation, and gravity field. We assess how well we know the rapid, submonthly portion of bottom pressure changes by analyzing output from oceanographic models and observations from the Gravity Recovery and Climate Experiment (GRACE) dual satellite mission. We show that two different GRACE solutions, sampled daily, are in good agreement with each other over the deep interior of the ocean basins. Moreover, bottom pressure changes simulated with a simple single‐layer model are remarkably consistent with GRACE, providing an independent measure of the quality of both products. Based on these grounds, and by aid of an approximate error assessment, we suggest that nonstandard daily GRACE fields are realistic enough to help identifying deficiencies in oceanographic models and guide solutions to these issues. We particularly highlight an overestimation of Southern Ocean bottom pressure variability in two widely used general circulation simulations and speculate on ways how to improve the underlying models. : Key Points: We rigorously compare daily Gravity Recovery and Climate Experiment (GRACE) gravity solutions with bottom pressure output from five ocean models at periods <60 days Southern Ocean mass‐field variability in current de‐aliasing model is too energetic; dedicated barotropic simulations better match GRACE Daily gravity fields have errors of 0.5–1.5 cm (water height) over basin interiors and may guide improvements to existing ocean models : Austrian Science Fund (FWF) http://dx.doi.org/10.13039/501100002428 : National Aeronautics and Space Administration (NASA) http://dx.doi.org/10.13039/100000104 : Deutsche Forschungsgemeinschaft (DFG) http://dx.doi.org/10.13039/501100001659